Coordination and thermophysical properties of select trivalent lanthanides in LiCl–KCl. Issue 21 (19th May 2022) - Fuller, Jon; Moon, Jeremy; Zhang, Jing; Chidambaram, Dev; An, Qi
Abstract : The coordination chemistry, thermophysical and transport properties, and vibrational density of states of three trivalent lanthanides in eutectic LiCl–KCl were evaluated using QM-MD and 2PT and compared with those of the experimental Raman spectra. Abstract : The coordination chemistry of various fission and decay products, such as actinides and lanthanides, are crucial to the commercial deployment of molten salt reactors as they can affect the thermophysical properties. Here, we examined the structure, coordination environment, and physical properties such as the density and the vibrational density of states for three lanthanide species, namely Ce, Eu, and Sm in the LiCl–KCl eutectic system using a combination of quantum mechanics simulations and spectroscopic experiments. Quantum mechanics molecular dynamics (QM-MD) modelling was employed to determine the physical properties of each system resulting in accurate local coordination of each species. Then, the vibrational density of states (DOS) was determined using a two-phase thermodynamic modelling which was then compared to the experimentally obtained Raman spectra of the species in molten LiCl–KCl having the eutectic composition. We find that Ce 3+, Eu 3+ and Sm 3+ all adopt octahedral local coordination environments in the eutectic salt composition in good agreement with experimental results. Ce 3+ is found to fluctuate between an octahedral six-coordinated and a seven-coordinated structure due to the increased local proximity of Cl in the eutectic salt, resulting in a lower fluidicity/diffusivity than the other trivalent lanthanides studied. The thermophysical properties of the eutectic composition with trivalent lanthanides were not significantly different from the pure eutectic salt composition, but several changes were noted.